English Students’ Motivation and Their Learning Styles in Speaking Class at Sawerigading University of Makassar - Nurfajriah Basri; Rahayu Rahayu (FOSTER: Journal of English Language Teaching, 2022)
ABSTRACT This research aimed to find out the correlation beetwen students’ motivation and their learning style in speaking subject. The questions of the research is “How does the correlation beetwen students motivation and their learning style in speaking class at the English Students of Sawerigading University of Makassar?”. Questionnaires were distributed to 42 students, while the questionnaire of students’ motivation and learning style consisted of 20 questions of each variable in the form of questions, from each of the questions was followed by 5 (five) alternative answers that consecutively very Strongly Agree (SA), Agree (A), Undecided (U), Disagree (D) and Strongly Disagree (SD) with consecutive scores 5,4,3,2 and 1. While the value obtained from the students’ motivation instrument. To get the data, researcher used a questionnaire with 20 items about distributed to 20 sample respondents. The result of findings about correlation between students’ motivation and their learning style in speaking class at the third semester students of Sawerigading University of Makassar, compared prices count with r-r- table. With the 5% significance level of 0.288 was obtained rtable rhitung at 0.882. When compared both rhitung = 0.882> rtable = 0.288, so that Ho accepted and Hi rejected or the correlation between students’ motivation and their learning style in speaking class was 0.882. This meant that correlation between them was strong correlation. Keywords : Motivation, Learning style. Speaking